Adaptation and Validation of the S-NutLit Scale to Assess Nutritional Literacy in the Peruvian Population - Chilón-Troncos, Rony Francisco (2023)
Maintaining good dietary practices is a factor that allows a better quality of life; therefore, it is necessary to promote health via the fundamental tool of nutritional literacy. In this context, this study aims to evaluate nutritional literacy in Peru through the S-NutLit tool, which is composed of two dimensions. The scale, composed of 11 items, was applied to 396 Peruvian adults. According to the evaluation of the indicators, an acceptable reliability was found, as was a model fit with excellent estimation according to its indicators (CMIN/DIF 2.559; IFC 0.965; SRMR 0.043; RMSEA 0.063; and PClose 0.070). In this way, we seek to reinforce health promotion activities through a nutritional literacy diagnosis, which, due to its characteristics, can be self-administered and used by health entities and other entities in general that are interested in knowing the eating practices of an individual, which undoubtedly leads to good health.